2021
DOI: 10.3390/w13212989
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Selected Water Quality Parameters in the Utrata River as a Function of Catchment Area Land Use

Abstract: Surface waters are very important for society, as they are a source of potable water, as well a water supply for agricultural, industrial and recreational purposes. This paper presents changes in the quality of the water in the Utrata River, along its entire length, as a function of the catchment area’s land use. Water-quality measurements were carried out once a month for a total period of one year (April 2019–March 2020) at 24 measurement points. The concentrations of the following compounds were measured: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 52 publications
5
15
0
Order By: Relevance
“…value as it will decrease as the organic pollutants increase in water, the lowest D.O. value was recorded in autumn at St. 2 which was (0.854 mg/l) and the highest was in winter with 6.527 and 6.5 mg/l at St.1 and St.2 respectively and that can be explained by the fact that as temperature decrease the dissolving of oxygen will increase [18] B.O.D. recorded the lowest value in winter with 1.280 and 1.2 mg/l at St.1 and St.2 respectively.…”
Section: Resultsmentioning
confidence: 97%
“…value as it will decrease as the organic pollutants increase in water, the lowest D.O. value was recorded in autumn at St. 2 which was (0.854 mg/l) and the highest was in winter with 6.527 and 6.5 mg/l at St.1 and St.2 respectively and that can be explained by the fact that as temperature decrease the dissolving of oxygen will increase [18] B.O.D. recorded the lowest value in winter with 1.280 and 1.2 mg/l at St.1 and St.2 respectively.…”
Section: Resultsmentioning
confidence: 97%
“…As a result, the authors suggested comparing this type of analysis with results attained by numerical models, as it could provide a better understanding of the nutrient system. In their work, Debska et al [27] analyzed the changes in water quality parameters depending on the land use of different areas in the considered catchment. To do so, they implemented monthly measurements along the River Utrata for one year.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical oxygen demand (COD), total nitrogen, and total phosphorus were selected as being the most important parameters to indicate the deterioration of the water quality in the drains and lake [48,49]. High concentrations of these parameters in waterways reduce the oxygen and cause overgrowth of algae and water plants in a way that leads to disturbance of the ecological balance of the aquatic system [50,51].…”
Section: Selection Of the Main Pollutants' Indicatorsmentioning
confidence: 99%